Resolution of Insurance Disputes from Defective Consent After Constitutional Court Decision - Asa Prayoga Jiwangga; Subekti; Ernu Widodo (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Human life is inseparable from concerns regarding the welfare of family members left behind after the death of the primary breadwinner. Insurance has become an integral part of modern human life, serving to maintain life balance and ensure the economic stability of families when the breadwinner passes away. The presence of life insurance is expected to provide financial protection so that the surviving family members may continue to live in adequate conditions. One of the fundamental principles in insurance law is the principle of utmost good faith. Therefore, consumers, in this case the insured, are required to disclose information fully and accurately. Failure to do so previously entitled the insurer to unilaterally cancel the insurance contract in accordance with Article 251 of the Commercial Code. However, the Constitutional Court of Indonesia, through Decision Number 83/PUU-XII/2024, declared that Article 251 of the Commercial Code is contrary to the 1945 Constitution of the Republic of Indonesia and therefore has no binding legal force. Accordingly, the legal issue examined in this study concerns how disputes arising from defects of consent committed by the insured should be resolved following the Constitutional Court Decision Number 83/PUU-XXII/2024. This research employs a normative legal research method. The study concludes that insurers may still cancel an insurance agreement if a defect of consent committed by the insured is proven, by filing a tort claim based on an unlawful act before the District Court.